Fenomena Gerhana dan Signifikansi Astronomi dalam Al-Qur’an - Al Fatih, Muhammad Shalahuddin; Zulfis; Faizin (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This article describes the phenomenon of a lunar eclipse and a solar eclipse from the perspective of the Koran and astronomy. This phenomenon has attracted human attention since ancient times and also has meaning and significance in Islamic teachings. In this paper, we carry out a scientific interpretation analysis of verses from the Koran related to lunar eclipses and solar eclipses. We explain how a lunar eclipse occurs when the Earth is between the Sun and the Moon, and how a solar eclipse occurs when the Moon is between the Earth and the Sun. This research uses the library research method by presenting interpretations from Al-Quran exegetes and relate it to modern astronomical knowledge. Apart from that, we also discuss the significance of astronomy in the Koran and the importance of studying knowledge about the universe in Islam. This article aims to increase Muslims' understanding of the relationship between religion and science, as well as to appreciate the wonders of the universe which reflect the greatness of Allah SWT. The results of this research show that knowledge about eclipses in Islamic religious sources is an important factor that makes Muslims aware of the significance of astronomy.